The role of Army Cyber Center in the Royal Thai Army Headquarters 2017-2022 - Phurithornjinda, Thatchakon; Pungprawat, Kriangchai; Boonlue, Nattapong; Sohheng, Nipon (The Journal of Development Administration Research, 2024)
This research aimed: 1) to study the roles, duties, missions, and scope of responsibilities of Army Cyber Center in the Royal Thai Army Headquarters 2017-2022; 2) to analyze and study the policy development guidelines of the Ministry of Defense, the Royal Thai Army Headquarters, Cyber ​​security aspect; and 3) to study the creation of new knowledge in cyber security management of the country. Use qualitative research Data were collected by studying information from important documents and in-depth interviews with 8 relevant experts. The research results found that: 1) roles include (1) the duties, roles and responsibilities of Army Cyber Center arise from the Royal Thai Army Establishment Act; (2) The establishment of the Royal Thai Army Headquarters relies on the cooperation of all armed forces to provide a one-dimensional picture of the battlefield; (3) proactive cyber operations to support government policy; and (4) The cyber departments of each military force are highly independent, making integration difficult, 2) the policy development found that: (1) the Ministry of Defense lacks human resources with expertise in Set standards for technology related to the cyber dimension to be effective; (2) the Ministry of Defense should not permit the separate procurement of terminal protection equipment; (3) the Ministry of Defense should not permit the procurement of discrete Internet-connected defense equipment; and (4) the Ministry of Defense's policy for purchasing operating systems and office utility programs should be procured as a whole. 3) the creation of new knowledge in cyber security management of the country. It was found that: (1) there is instability in the organization regarding government regulations; (2) dimension of international cooperation in cyber security; (3) the Government should establish cyber curricula and knowledge for schools and universities, and (4) Thailand still lacks an agency that is instrumental in solving cyber problems for people in the area.